Notary's Responsibility for Deeds Declared Void or Invalid Based on Court Decision - Aswin, Muhammad; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze: 1) The notary's responsibility for deeds declared null and void based on a court decision. 2) Legal protection for the parties, including notaries, when the deed made is declared null and void. This type of research falls within the scope of normative legal research. The approach method in this research is legislation (statue approach). The type of data in this research is secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses library techniques (document study). The analysis in this research is prescriptive. The results of the study concluded: 1) The notary's responsibility for deeds declared null and void based on a court decision is relative and is determined by the notary's level of compliance with legal provisions and the application of the prudential principle. This responsibility can include civil, administrative, and criminal aspects, depending on the presence or absence of elements of error or negligence in carrying out the authority of his position. In Decision Number 43/Pdt.Sus-Gugatan Lain-Lain/2023/PN Niaga Semarang, the cancellation of a deed does not give rise to responsibility for the notary because no formal error was found; Violations occur in the substance of bankruptcy law by the parties, not by the notary. 2) Legal protection for the parties, including notaries, when the deed they have made is declared null and void or invalid aims to ensure legal certainty and justice. Protection for the parties is realized through a court decision that restores violated rights, while for notaries it is provided if they have carried out their official duties in accordance with the Notary Law (UUJN) and the principle of good faith. Legal protection mechanisms include preventive protection through supervision by the Notary Supervisory Board (MPN) and the Notary Honorary Council (MKN), as well as repressive protection through the courts and professional rehabilitation if the notary is not proven guilty. Proportional legal protection ensures a balance between upholding official responsibilities and guaranteeing the independence of the notary profession in carrying out its state function as a guarantor of legal certainty.